937. Factors Associated with Metabolic Syndrome in People with HIV under 40 Years in Guatemala. (31st December 2020) - Marroquín, Hugo E; Ortiz, Dean; Larson, Lindsey; Franco, Katherine; Spec, Andrej; Melendez, Johanna; Pinzon, Rodolfo; Mejia-Chew, Carlos; Samayoa, Johanna; O'Halloran, Jane A
Abstract: Background: HIV infection and antiretroviral therapy (ART) can lead to metabolic abnormalities associated with increased cardiovascular disease risk, some of these abnormalities (central obesity, elevated fasting glucose, triglycerides, and blood pressure and low HDL cholesterol) are in metabolic syndrome (MetS). The prevalence of MetS increases with age. Currently, the status of MetS in people with HIV (PWH) Guatemala is unknown. We assessed the prevalence of MetS and potential predictors in PWH participating in prospective cohort study at Hospital Roosevelt in Guatemala City. Methods: We performed a cross-sectional analysis of PWH under 40 years old receiving ART for at least 6 months from July 2019 to March 2020. The harmonized criteria for MetS and the cut-off for waist circumference recommended by the Latin American Diabetes Association were used. Association between MetS and gender, place of residency, ethnicity, educational level, baseline and current CD4 count, smoking, alcohol consumption, physical activity, viral load, body mass index (BMI) and ART exposure was assessed in bivariate analysis. Potential predictors (p-value < 0.1) were included in a multivariate binary logistic regression model. Results: Of total cohort of 757 participants enrolled390 (51.5%) were younger than 40 years. Of those under < 40 years, 150 (38.5%) were women, 59 (15.1%) Mayan, median age was 32 years (IQR 27, 37). 93 (23.8%) had MetS. Between group differences in Table 1. Of those with Met, 51 (54.8%) had elevated waist circumference, 87 (93.5%) elevated triglycerides, 83 (89.2%) low HDL-c, 56 (60.2%) elevated blood pressure and 35 (37.6%) elevated fasting glucose. Body mass index (BMI) ≥ 25 kg/m 2 or higher and 2 years or more of cumulative non-nucleoside reverse transcription inhibitors (NNRTI) where more common in those < 40 years with MetS compared to those without MetS. On multivariable regression, MetS was associated with current CD4 count < 200 (OR 3.1; IC 1.51, 6.34; p-value < 0.01) and BMI ≥ 25 kg/m 2 (OR; 6.53; IC 3.64, 11.73; p-value < 0.01). Table1. Between group differences (No MetS vs MetS) Conclusion: Nearly one in every four PWH under 40 years old in our cohort was affected by MetS. Dyslipidemia (elevated triglycerides and low HDL-c) was the main driver of MetS. Lower CD4 count and overweight were predictors for MetS in PWH under 40. Disclosures: Andrej Spec, MD, MSCI, Astellas (Grant/Research Support)Mayne (Consultant)Scynexis (Consultant)